Neuron-derived neurotrophic factor promotes the differentiation of intramuscular and subcutaneous adipocytes in goat - An Li; Youli Wang; Ruiwen Li; Yaqiu Lin; Yanyan Li; Yong Wang; Wei Liu; Xiong Yan (Animal Biotechnology)
Adipocyte play an important role in human health and meat quality by influencing the tenderness, flavor, and juiciness of mutton It has been shown that neuron-derived neurotrophic factor (NENF) is closely related to energy metabolism and adipocyte differentiation in bovine. However, the role of NENF in the goats remains unclear. The aim of this study was to detect the expression of NENF in goat subcutaneous and intramuscular adipocytes, temporal expression profiles of the NENF, and overexpressed NENF on the differentiation of different adipocytes. In this study, PCR amplification successfully cloned the goat NENF gene with a fragment length of 521 bp. In addition, the time point of highest expression of NENF differed between these two adipocytes differentiation processes. Overexpression of NENF in intramuscular and subcutaneous adipocytes promoted the expression levels of differentiation markers CEBPβ and SREBP, which in turn promoted the differentiation of intramuscular and subcutaneous adipocytes. This study will provide basic data for further study of the role of goats in goat adipocyte differentiation and for the final elucidation of its molecular mechanisms in regulating goat adipocyte deposition.